2012
DOI: 10.1103/physrevb.86.059905
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Al doping effect on magnetic phase transitions of magnetoelectric hexaferrite Ba0.7Sr1.3Zn

Abstract: Previously we have published the paper titled "Al doping effect on magnetic phase transitions of magnetoelectric hexaferrite Ba 0.7 Sr 1.3 Zn 2 (Fe 1−x Al x ) 12 O 22 " in Physical Review B. Recently, we found that the equation (A4) presented in the Appendix of the paper contains a typographical error. The original equation in the paper containing the error is as follows:The correct form of the equations must be as follows:The error is limited to the last line corresponding to the C and D parameters. The above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Thus, the ME multiferroics are expected to be applicable for new electronic devices. Among a variety of ME multiferroics, hexaferrites are supposed to be the most promising materials for the device application, because they exhibit ferroelectricity associated with noncollinear magnetic orders in relatively low magnetic field and high temperature regions [3][4][5][6][7][8][9][10][11][12][13] . In the present study, we focus on a Y-type hexaferrite BaSrCo 2 Fe 11 AlO 22 (BSCo-FAO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ME multiferroics are expected to be applicable for new electronic devices. Among a variety of ME multiferroics, hexaferrites are supposed to be the most promising materials for the device application, because they exhibit ferroelectricity associated with noncollinear magnetic orders in relatively low magnetic field and high temperature regions [3][4][5][6][7][8][9][10][11][12][13] . In the present study, we focus on a Y-type hexaferrite BaSrCo 2 Fe 11 AlO 22 (BSCo-FAO).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we refer to the magnetic moment in ith L (S) block as S L i (S S i ). On the basis of the block approximation, we depict schematic magnetic structures reported in the previous studies on the Y-type hexaferrites 4,12,[18][19][20] in Figs. 1(b)-1(e).…”
Section: Introductionmentioning
confidence: 99%
“…As x increases, the critical magnetic field for switching electric polarization is systematically reduced down to an extremely small 10 mT (100 G), and the ME susceptibility is greatly enhanced to reach a giant value of 2 9 10 4 ps m -1 at an optimum x = 0.08 [83]. When x = 1.0, the heliconical state collapses, due to competition between easy-axis and easy-plane anisotropies [83]. It is suggested that this giant magnetoelectricity occurs because the Al substitution progressively stabilises a longitudinal heliconical state, as opposed to the helical spin phase seen in unsubstituted BSZY (Fig.…”
Section: ) [76] This Was Particularly Apparent For the Phase Changesmentioning
confidence: 98%
“…The ME properties of Ba 0.5 Sr 1.5 Me 2 Fe 12 O 22 hexaferrite are reported to be modified when the Fe 3 þ ions are replaced with Al 3 þ ions [17,18]. The fundamental crystal structure of this system belongs to the R-3m space group with hexagonal structure.…”
Section: Introductionmentioning
confidence: 98%